Review of Impact of Dooshi Visha on Female Infertility - Anaghashree, S; Chaitra , H (International Research Journal of Ayurveda & Yoga, 2022)
Dooshi visha is a unique concept mentioned in Ayurveda, which has the potential to accumulate in various bodily tissues depending on their affinity and harm the body, by causing chronic illness. Present day exposure to various harmful chemicals can be considered as dooshi visha as they get accumulated in bodily tissues leading to cumulative toxicity causing chronic illnesses, instead of causing death immediately. Chemicals acting over the female reproductive system at different doses of exposure, and concept of dooshi visha was studied thoroughly. Chemicals having their affinity towards female reproductive system was found to cause significant harmful effects like infertility when exposed above permissible limit for longer durations, hence it can be considered as dooshi vishas. Incidences of chemical exposure and female infertility is increasing proportionally. Present day female reproductive problems viewed in the perspective of dooshi visha and treating accordingly may subside the present days female reproductive problems. Hence, present paper focuses on impact of dooshi visha on female fertility.